FLASH: a next-generation CRISPR diagnostic for multiplexed detection of antimicrobial resistance sequences. Issue 14 (22nd May 2019) - Quan, Jenai; Langelier, Charles; Kuchta, Alison; Batson, Joshua; Teyssier, Noam; Lyden, Amy; Caldera, Saharai; McGeever, Aaron; Dimitrov, Boris; King, Ryan; Wilheim, Jordan; Murphy, Maxwell; et al.
Abstract: The growing prevalence of deadly microbes with resistance to previously life-saving drug therapies is a dire threat to human health. Detection of low abundance pathogen sequences remains a challenge for metagenomic Next Generation Sequencing (NGS). We introduce FLASH (Finding Low Abundance Sequences by Hybridization), a next-generation CRISPR/Cas9 diagnostic method that takes advantage of the efficiency, specificity and flexibility of Cas9 to enrich for a programmed set of sequences. FLASH-NGS achieves up to 5 orders of magnitude of enrichment and sub-attomolar gene detection with minimal background. We provide an open-source software tool (FLASHit) for guide RNA design. Here we applied it to detection of antimicrobial resistance genes in respiratory fluid and dried blood spots, but FLASH-NGS is applicable to all areas that rely on multiplex PCR.